STRATEGI PEMBINAAN SUMBER DAYA MANUSIA DI POLRES KOTA METRO DALAM MEMBANGUN CITRA POLRI PADA MASYARAKAT - Intan Destrilia; Yuditya Wardhana (Sawala : Jurnal Administrasi Negara, 2024)
The negative image of the Indonesian National Police as a whole has an impact on the police on duty at the Metro City Police, therefore when carrying out their duties as law enforcers, the Indonesian National Police do not only focus on operational aspects of services but pay more attention to image and relations with the community, to carry out this, the Indonesian National Police must also carry out internal and external human resource development so as to ensure the quality of the police in carrying out their duties as they should. The purpose of this study is to describe and analyze human resource development strategies at the Metro Police in building the image of the Indonesian National Police. The method used by the researcher is a qualitative approach and the data collection techniques used in this study are interviews and document studies. From the results of the study, it can be concluded that human resource development in building the image of the Indonesian National Police can be done by providing direction for continuing education and training as an effort to improve the intellectual and personality abilities of an employee in achieving the objectives of the Function, as well as psychological, mental, moral, legal development as a basis for building the image of the Indonesian National Police.